1980
DOI: 10.1139/b80-038
|View full text |Cite
|
Sign up to set email alerts
|

Phytohormone changes in Bouteloua gracilis infected by vesicular–arbuscular mycorrhizae: I. Cytokinin increases in the host plant

Abstract: Bouteloua gracilis was grown in defined, axenic culture with and without vesicular–arbuscular (VA) mycorrhizae. Leaves and roots of mycorrhizal and nonmycorrhizal plants were harvested and assayed for cytokinin content using a soybean callus tissue bioassay. Total cytokinin activity was 57 and 111% greater in leaves and roots, respectively, in mycorrhizal over control plants. Cytokinin activities, separated using paper chromatography with water saturated n-butanol as a solvent, doubled in roots and leaves at R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
0
5

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(91 citation statements)
references
References 8 publications
5
81
0
5
Order By: Relevance
“…Some research has also shown that symbiosis with AM fungi results in the increase of terpenoids and phenolic acids, which may result from increased absorption of mineral nutrients, especially P and N (Kapoor et al 2002a, b;Toussaint et al 2007). Finally, changes in the secondary metabolites of mycorrhizal plants may result from changes in levels of phytohormones like cytokinin or gibberellin (Allen et al 1980(Allen et al , 1982Copetta et al 2006;Kapoor et al 2007;Toussaint 2007). However, these and other possibilities all remain to be verified (Toussaint 2007).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…Some research has also shown that symbiosis with AM fungi results in the increase of terpenoids and phenolic acids, which may result from increased absorption of mineral nutrients, especially P and N (Kapoor et al 2002a, b;Toussaint et al 2007). Finally, changes in the secondary metabolites of mycorrhizal plants may result from changes in levels of phytohormones like cytokinin or gibberellin (Allen et al 1980(Allen et al , 1982Copetta et al 2006;Kapoor et al 2007;Toussaint 2007). However, these and other possibilities all remain to be verified (Toussaint 2007).…”
Section: Discussion and Perspectivesmentioning
confidence: 99%
“…6, see also Fig. 2), suggesting that VA mycorrhizal infection may induce changes of the phyto-hormonal level in plants to prolong the leaf life span (ALLEN et al 1980). This phenomenon may be advantageous especially for chickpea seed production as compared to other grain legumes (SINGH and PANDEY 1980).…”
Section: Methodsmentioning
confidence: 94%
“…In VA mycorrhizal plants, root and leaf tissue ABA levels were reduced (Allen, Moore & Christensen, 1982) and cytokinin levels were increased in root and leaf tissue (Allen, Moore & Christensen, 1980;Dixon, Garrett & Cox, 1988 a) and in sap (Dixon, Garrett & Cox, 19886). In our results neither P nor mycorrhizal treatments affected ABA levels in xylem sap.…”
Section: Plant-growth Substancesmentioning
confidence: 99%